Analysis of the Performance Allowance System in Improving Employee Performance - Rajab, Isra; Syaifuddin, Dedy Takdir; Hakim, Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study investigates the effectiveness of the performance allowance system at PD. BPR Bahteramas Konawe in improving employee performance. The research explores the roles of transparency, fairness, and flexibility within the system and assesses its impact on employee motivation and productivity. The main issue addressed is identifying the key factors that influence the relationship between the allowance system and the achievement of organizational goals. The purpose of this research is to provide management with recommendations to refine the performance allowance system, enabling the company to achieve its strategic objectives and enhance its competitiveness in the financial sector. The study uses descriptive qualitative analysis with interviews as the primary data collection tool. The analysis focuses on important themes gathered from insights provided by the Chief Executive Officer, Operations Manager, and staff from various divisions. The findings reveal that the performance allowance system significantly enhances employee performance by offering both financial and non-financial incentives that recognize individual contributions. Success depends on setting clear targets, maintaining transparent evaluations, and utilizing technology for accurate assessments